Inflation targeting in low‐income countries: Does IT work?. Issue 4 (9th July 2020) - Morozumi, Atsuyoshi; Bleaney, Michael; Mumuni, Zakari
Abstract: Previous research on inflation targeting (IT) has focused on high‐income countries and emerging market economies (EMEs). Only recently have sufficient data accumulated for the performance of IT in low‐income countries (LICs) to be assessed. We show that IT has not so far been as effective in reducing inflation in LICs as in EMEs. Relatively low central banks' instrument independence in LICs, associated with weak restrictions limiting a central bank's lending to the government, helps explain this result.